A reduced graphene oxide-Fe3O4 composite functionalized with cetyltrimethylammonium bromide for efficient adsorption of SARS-CoV-2 spike pseudovirus and human enteric viruses. (March 2022) - Zhou, Shuqing; Jin, Min; Tan, Rong; Shen, Zhiqiang; Yin, Jing; Qiu, Zhigang; Chen, Zhengshan; Shi, Danyang; Li, Haibei; Yang, Zhongwei; Wang, Huaran; Gao, Zhixian; et al.
Abstract: The latent dangers of waterborne viral transmission have become a major public health concern. In this study, reduced graphene oxide (rGO)-Fe3 O4 nanoparticles were decorated with cetyltrimethylammonium bromide (CTAB) to adsorb severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike pseudovirus and three human enteric viruses (HuNoV, HRV, and HAdV). The successful combination of CTAB with rGO-Fe3 O4 was confirmed by transmission electron microscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, zeta potential, Brunner-Emmet-Teller, and vibrating sample magnetometer measurements. The adsorption of HuNoV and HAdV followed pseudo-first-order kinetics, while that of HRV conformed to the pseudo-second-order model. CTAB-functionalized rGO-Fe3 O4 exhibited exceptionally high adsorption of HuNoV, HRV, HAdV and SARS-CoV-2 spike pseudovirus, with maximum adsorption capacities of 3.55 × 10 7, 7.01 × 10 7, 2.21 × 10 7 and 6.92 × 10 6 genome copies mg −1, respectively. Moreover, the composite could effectively adsorb the four types of virus particles from coastal, tap, and river water. In addition, concentrating the virions using CTAB functionalized rGO-Fe3 O4 composites before qPCR analysis significantly improved the detection limit. The results indicate that viruses are captured on the surface of CTAB functionalized rGO-Fe3 O4 composites through electrostatic interactions and the intrinsic adsorption ability of rGO. Overall, CTAB-functionalized rGO-Fe3 O4 composites are promising materials for the adsorption and detection of human enteric viruses as well as SARS-CoV-2 from complex aqueous environments. Graphical abstract: Image 1 Highlights: Functionalized reduced graphene oxide-Fe3 O4 was prepared to adsorb virus particles from water. The adsorbents show exceptionally high adsorption capacities towards HuNoV, HRV, HAdV and SARS-CoV-2 Spike Pseudovirus. The composite could effectively adsorb the four virus species from coastal, tap, and river water. Concentrating virus using composites before qPCR analysis can significantly improve detection limit.